Pac-man motility of kinetochores unleashed by laser microsurgery - LaFountain, James R. (The American Society for Cell Biology, 2012)
We report on experiments directly in living cells that reveal the regulation of kinetochore function by tension. X and Y sex chromosomes in crane fly (Nephrotoma suturalis) spermatocytes exhibit an atypical segregation mechanism in which each univalent maintains K-fibers to both poles. During anaphase, each maintains a leading fiber (which shortens) to one pole and a trailing fiber (which elongates) to the other. We used this intriguing behavior to study the motile states that X-Y kinetochores are able to support during anaphase. We used a laser microbeam to either sever a univalent along the plane of sister chromatid cohesion or knock out one of a univalent's two kinetochores to release one or both from the resistive influence of its sister's K-fiber. Released kinetochores with attached chromosome arms moved poleward at rates at least two times faster than normal. Furthermore, fluorescent speckle microscopy revealed that detached kinetochores converted their functional state from reverse pac-man to pac-man motility as a consequence of their release from mechanical tension. We conclude that kinetochores can exhibit pac-man motility, even though their normal behavior is dominated by traction fiber mechanics. Unleashing of kinetochore motility through loss of resistive force is further evidence for the emerging model that kinetochores are subject to tension-sensitive regulation.